Corporate tax avoidance and firm value - Desai, Mihir A. 1968-; Dharmapala, Dhammika (National Bureau of Economic Research <Cambridge, Mass.>: NBER working paper series, 2005)
"How do investors value managerial actions designed solely to minimize corporate tax obligations? Using a framework in which managers' tax sheltering decisions are related to their ability to divert value, this paper predicts that the effect of tax avoidance on firm value should vary systematically with the strength of firm governance institutions. The empirical results indicate that the average effect of tax avoidance on firm value is not significantly different from zero; however, the effect is positive for well-governed firms as predicted. Coefficient estimates are consistent with an expected life of five years for the devices that generate these tax savings for well-governed firms. Alternative explanations for the dependence of the valuation of the tax avoidance measure on firm governance do not appear to be consistent with the empirical results. The findings indicate that the simple view of corporate tax avoidance as a transfer of resources from the state to shareholders is incomplete, given the agency problems characterizing shareholder-manager relations"--National Bureau of Economic Research web site.